The Role of Thrombocytosis as a Prognostic Factor for Epithelial Ovarian Cancer - Andrijono; Heru Prasetyo; Eka R Gunardi; Gatot Purwoto; Hariyono Winarto (Indonesian Society of Obstetrics and Gynecology, 2021)
Objective: To determine whether thrombocytosis is a prognostic factor for epithelial ovarian cancer and its relationship with 3-year overall survival in epithelial ovarian cancer patients. Methods: This study is a retrospective cohort study using medical record of patients with epithelial ovarian cancer registered in cancer registry of Oncology Division in Obstetrics and Gynecology Department, Dr. Cipto Mangunkusumo National General Hospital from January 2014 - July 2016. Data were collected when subjects were first until diseases outcomes identified in 3 years. Results: : Out of 220 subjects, 132 (60%) were patients with advanced stage epithelial ovarian cancer (stage II/III/IV). 94 (42.7%) subjects had thrombocytosis. Patients with advanced stage of disease had higher risk of having thrombocytosis than the ones with earlier stage (p=0.005; OR=2.329). Correlation between thrombocytosis and 3-year overall survival was known to be insignificant (p=0.555). There was shorter mean time survival between patients with thrombocytosis and the ones without but the there was no significant difference in hazard ratio between the two groups (p  = 0.399). Conclusion :Thrombocytosis is not a prognostic factor in patients with epithelial ovarian cancer. There is also no significant difference of 3-year overall survival between patients with or without thrombocytosis. Keywords: epithelial ovarian carcinoma, prognosis,  thrombocytosis.   Abstrak Tujuan: Membuktikan bahwa trombositosis sebagai faktor prognosis kesintasan pada pasien kanker ovarium jenis epitelial dan hubungannya terhadap kesintasan 3 tahun pasien kanker ovarium  jenis epitelial. Metode: Penelitian ini merupakan studi kohort retrospektif menggunakan data rekam medis pasien kanker ovarium epitelial yang terdaftar pada cancer registry Departemen Obstetri dan Ginekologi Divisi Onkologi Rumah Sakit Cipto Mangunkusumo pada tahun Januari 2014-Juli 2016. Pengamatan dilakukan saat subjek pertama kali didiagnosis akhir pengamatan selama 3 tahun. Hasil: Didapatkan 220 subjek penelitian yang merupakan populasi terjangkau dan memenuhi kriteria inklusi dan eksklusi. Dari 220 subjek penelitian, 132 (60%) dari 220 subjek penelitian merupakan pasien dengan kanker ovarium stadium lanjut (Stadium II/III/IV). Trombositosis didapatkan pada 94 orang subjek penelitian (42,7%). Pasien dengan kanker stadium lanjut memiliki risiko trombositosis yang lebih tinggi dibandingkan subjek pada stadium awal (p=0,005;OR=2,329). Trombositosis secara statistik tidak bermakna pada kesintasan 3 tahun (p=0,555). Terdapat mean time survival yang lebih rendah pada pasien dengan trombositosis tetapi tidak ada perbedaan hazard ratio yang bermakna antara subjek dengan atau tanpa trombositosis (p=0,399). Kesimpulan : Trombositosis bukan merupakan faktor prognostik pada pasien kanker ovarium jenis epitelial dan tidak terdapat hubungan antara trombositosis dan 3 tahun pada pasien dengan kanker ovarium jenis epithelial. Kata kunci: karsinoma ovarium epithelial,  prognosis, trombositosis